2015
DOI: 10.1142/s2010007815500189
|View full text |Cite
|
Sign up to set email alerts
|

Individual Discount Rates and Climate Change: Is Discount Rate Associated With Support for a Carbon Tax?

Abstract: The issue of climate change is often framed as one in which contemporary actions, often with affixed costs, are necessary in order to prevent even greater costs being paid during a period in the future. Under such a framework it is thus necessary to calculate the rate in which future benefits are discounted to reflect current values. In this paper we examine how individual level discount rates affect their support for a policy tool that incurs contemporary costs in an effort to prevent future environmental dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Agrawal et al [70] conclude that white voters were less likely than non-whites to support environmental taxes. In contrast, Amdur et al [71] show that nonwhite individuals are significantly less likely to support a carbon tax than Caucasians. A carbon tax policy that includes health insurance and free college builds more support for African Americans and Hispanics than white [16].…”
Section: Demographicmentioning
confidence: 88%
See 3 more Smart Citations
“…Agrawal et al [70] conclude that white voters were less likely than non-whites to support environmental taxes. In contrast, Amdur et al [71] show that nonwhite individuals are significantly less likely to support a carbon tax than Caucasians. A carbon tax policy that includes health insurance and free college builds more support for African Americans and Hispanics than white [16].…”
Section: Demographicmentioning
confidence: 88%
“…The majority of studies show that younger people give more support than older citizens (e.g., [31,60,68]). In contrast, Agrawal et al [70], Amdur et al [71], and Thalmann [55] found the older people have more support toward environmental taxes. At the same time, Hammar and Jagers [68] explains that the 31-60 age group is more negative than other age groups.…”
Section: Demographicmentioning
confidence: 92%
See 2 more Smart Citations
“…Second, these approaches do not easily address the fact that Republican supporters were once as likely to believe climate science as Democrats (Krosnick et al, 2000). Last, it is peculiar that the most market-friendly way to reduce emissions, carbon pricing, is much less popular among Republicans than Democrats, and this is true even with revenue recycling (Amdur, Rabe, & Borick, 2014). In broader strokes, most people who label themselves as very conservative are anything but on many fiscal issues (Barber & Pope, 2018; Drutman, 2017).…”
mentioning
confidence: 99%